2003
DOI: 10.1089/089771503322144581
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Recruitment Follows the Pattern of Inducible Nitric Oxide Synthase Expression in a Model for Carpal Tunnel Syndrome

Abstract: Chronic nerve compression (CNC) induces a permeability change in neural vasculature. As recent evidence has shown that an alteration in reactive oxidative species (ROS) is related to neural degradation and regeneration, we evaluated whether inducible nitric oxide synthase (iNOS) plays a role in a rat model for CNC. Semi-quantitative analysis of iNOS mRNA and protein were performed with in situ hybridization and immunohistochemistry, respectively, at 3, 5, and 9 months post-operatively. At 3 months, iNOS mRNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
4
19
1
Order By: Relevance
“…In Sommerich’s study, the significant decline in NCV (25–31%) induced by their repetitive task recovered to normal levels after cessation of the task. In contrast, Gupta and colleagues found no recovery after a 65% reduction in NCV even after 12 months of rest (Gupta et al, 2003). We have not yet examined the effects of rest in our model.…”
Section: Discussionmentioning
confidence: 99%
“…In Sommerich’s study, the significant decline in NCV (25–31%) induced by their repetitive task recovered to normal levels after cessation of the task. In contrast, Gupta and colleagues found no recovery after a 65% reduction in NCV even after 12 months of rest (Gupta et al, 2003). We have not yet examined the effects of rest in our model.…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous studies have demonstrated a massive proliferation of Schwann cells in peripheral nerve segments subjected to sustained mechanical stimulation. [22][23][24][25] This proliferative response is accompanied by sprouting of undamaged axons, suggesting that Schwann cells are activated in a way that promotes axonal growth. To date, there has been limited study focusing on the role of these mechanically stressed Schwann cells in a spinal cord injury model by creating a permissive, pro-regenerative behavior.…”
mentioning
confidence: 99%
“…Sprague-Dawley rats (n ϭ 30) served as donors for preconditioned and control sciatic nerve grafts as described previously. 23 Briefly, sciatic nerves were exposed using the gluteal splitting approach. The control nerve segments were simply exposed, while with the experimental group, the sciatic nerves were compressed with inert, nonconstrictive tubing with inner diameter 1.3 mm, to create chronic nerve compression.…”
mentioning
confidence: 99%
“…We also reported that preoperative CSF NO x levels are useful as a quantitative predictor for postoperative pain relief in LCS [12]. Although little is known about the origin of NO x in LCS, iNOS protein and its encoding mRNA have been detected at the constriction site in some studies using peripheral nerve compression models [13][14][15]. These findings suggest that elevated CSF NO x levels in LCS patients are derived from iNOS that is induced at the compressed cauda equina or nerve roots.…”
Section: Introductionmentioning
confidence: 72%